A fretting fatigue setup for testing shrink-fit connections and experimental evidence of the strength enhancement induced by deep rolling. (May 2016) - Bertini, L; Santus, C; Merlo, A; Bandini, M
Fretting tests are usually performed on flat specimens with lateral contacting pads. The shrink-fitted connection, which experiences fretting at the edge of the contact, prompted the alternative use of a round-shaped specimen. This simplified the equipment and provided an accurate alignment between the fretting specimen and the external hub which plays the role of the pad. The deep rolling treatment can also be efficiently applied to a round shape, which would otherwise be difficult on the flat specimen geometry. After introducing this solution for fretting testing, the paper shows an experimental campaign on three shrink-fitted connections with different sizes and material combinations. There was a significant improvement in fretting fatigue strength, induced by the deep rolling, for all three specimen types. Finally, scanning electron microscopic analyses provided insights into the fretting fatigue nucleation mechanisms both for untreated and deep-rolled specimens.